Development of Process Recipes for Maximum Mask Etch Selectivity and Maximum Etch Rate Having Vertical Sidewalls for Deep, Highly-Anisotropic Inductively-Coupled Plasma (ICP) Etching of Fused Silica. (14th September 2017) - Pedersen, Michael; Huff, Michael
Abstract : Research conducted to develop Inductively-Coupled Plasma (ICP) etch processes is reported to allow the etching of deep, highly-anisotropic features into fused silica. To develop these etch processes, we conducted a Design of Experiments (DOE), whereby those parameters of the etch process having the most impact were varied over pre-defined values while leaving the other etch process settings unchanged. After each etch, the substrates were inspected to measure the results. Using the data collected, multiple regression analysis was conducted with the purpose of developing an accurate model of the process. This model was used to derive process parameter values to obtain the optimized etch results reported herein, including: an optimized recipe for attaining a maximum mask etch selectivity with etched features having vertical sidewalls (i.e., high anisotropy); and, an optimized recipe for maximum etch rate into fused silica with etched features having vertical sidewalls. Using the optimized recipes from the model developed, etching of very deep features (e.g., more than 100 microns) into fused silica with nearly vertical sidewalls was demonstrated.